Effect of Different Cooling Methods on the Quality of Low-temperature Cooked Pork - Wenyan WANG; Yan HAN; Yaxin YANG; Zimeng YUAN; Zhen WEI; Guoyuan XIONG; Linwei YANG (Shipin gongye ke-ji, 2023)
The study investigated the quality changes of low-temperature (80 ℃) pork cooled from 80 ℃ to 10 ℃ by refrigerated cooling (RC) (4 ℃), frozen cooling (FC) (−18 ℃) and vacuum refrigerated cooling (VRC) (4 ℃) respectively by measuring cooling rate, mass loss rate, texture, color and thiobarbituric acid (TBA) value. Furthermore, the TBA value and odor of pork cooled by above three cooling methods was also studied during storage at 4 ℃. The results showed that the cooling rate of VRC and FC were significantly higher than that of RC (P<0.05). The highest and the lowest mass loss were observed in RC (6.67%) and FC (4.47%) (P<0.05) separately. VRC had minimum L*, a* and maximum b* (P<0.05). And FC had maximum hardness (13647.14±51.47 g) (P<0.05). The odor of VRC was different from that of the other two treatments. The TBA values of RC products were significantly higher than the other two treatments at the end of cooling and during storage (P<0.05). As storage time increased, the difference in odor among the three treatments of samples became greater. FC and VRC could produce favorable quality low-temperature cooked pork with pleasant storage quality.